The impact of entrepreneurial orientation, financial literacy, and financial technology on SME business performance: The mediating role of risk management practices - Oktora, Yekie Senja; Pratikto, Heri; Restuningdiah, Nurika; Winarno, Agung (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the impact of entrepreneurial orientation, financial literacy, and financial technology on the business performance of SMEs, with risk management practices serving as a mediating variable. The research focuses on culinary SMEs in the Malang Raya area, utilizing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that entrepreneurial orientation, financial literacy, and financial technology significantly influence risk management practices. However, only entrepreneurial orientation has a direct and significant positive effect on business performance, while financial literacy and financial technology do not show a significant direct impact. Risk management practices are proven to significantly mediate the relationships between the independent variables and business performance. These findings highlight the importance of strengthening risk management practices to maximize the impact of various internal capabilities in enhancing the competitiveness and sustainability of SMEs.